Medios de comunicación de Iberoamérica en la Web Caso Bolivia - Jaramillo Briceño, Mishell Estefania (2018)
Abstract:This research work looks at the architecture of Ibero-America's digital media, its operation and positioning. The case study of this thesis is Bolivia, territory in which eight media are located between traditional and digital natives. The methodology used is mixed (qualitative and quantitative). The information is collected in a period of one month, the selection of the days is done by the compound week method. The study indicators are: accessibility, hypertextuality, interactivity, multimedia, continuous updating and personalization, elements that characterize digital journalism. The observation is complemented by the study of the morphology of the medium, social networks and the use of external platforms as content support.